PENGARUH KONSEP DIRI DAN LOCUS OF CONTROL TERHADAP MOTIVASI BERPRESTASI - Eko Sujadi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
Achievement motivation needs to be possessed by every individual. The aims of this research are to find out the effect of self concept and locus of control to achievement motivation in Islamic Guidance and Counseling Students of IAIN Kerinci. This research was descriptive & correlation research by using quantitative approach. Data were collected by using the Tennessee Self Concept Scale by William H. Fitts modified by Julia Raymod Lorenz, inventory Rotters Internal-External Locus of Control (I-E Scale), and achievement motivation scale. The data were analyzed by percentage technique, simple linear regression technique, and multiple linear regression technique. The finding of research are: 1) the general level of self concept is in middle category, 2) locus of control is in the middle range between internal locus of control and external locus of control with an average as big as 11.46, 3) the general level of achievement motivation is in middle category, 4) there is an effect self concept to achievement motivation, 5) there is an effect locus of control to achievement motivation, and 6) there is an effect self concept and locus of control to achievement motivation.